Harvest interval for phytomass production of peppermint transplanted in summer and winter - de Souza, Jéssica Maronez; Cargnelutti Filho, Alberto; Mario Márcio Neu, Ismael; Pereira Camargo, Darcila; Fillipin Osmari, Bruno; Fillipin Osmari, Lucas (Comunicata Scientiae, 2022)
The objective of this study was to determine the appropriate harvest interval for the phytomass production of peppermint (Mentha x piperita L.) transplanted in summer and winter. Two experiments were carried out in soilless cultivation, one with transplantation in summer and the other with transplantation in winter, in a completely randomized design, with five harvest intervals (30, 45, 60, 72, and 90 days) and four replicates. Fresh and dry matter weights of leaves, branches and shoots were determined. The fresh matter weight of peppermint leaves and the daily growth rate of this trait were similar between the harvest intervals for the transplantation performed in the summer. The dry matter weight of leaves was higher for the intervals of 72 days (90.80 g plant-1) and 90 days (90.24 g plant-1). For the transplantation performed in winter, the fresh matter and dry matter weights of leaves were higher for the intervals of 60 days (660.54 g plant-1, 107.14 g plant-1) and 90 days (630.40 g plant-1, 105.95 g plant-1). The same was observed for the daily growth rates of these traits. Peppermint harvests at 60-day intervals in winter transplantation are more appropriate for phytomass production. In summer transplantation, one can opt for the 45-day interval.